Systemic Sclerosis Dermal Fibroblasts Induce Cutaneous Fibrosis Through Lysyl Oxidase–like 4: New Evidence From Three‐Dimensional Skin‐like Tissues. Issue 5 (4th April 2020) - Huang, Mengqi; Cai, Guoshuai; Baugh, Lauren M.; Liu, Zhiyi; Smith, Avi; Watson, Matthew; Popovich, Dillon; Zhang, Tianyue; Stawski, Lukasz S.; Trojanowska, Maria; Georgakoudi, Irene; Black, Lauren D.; et al.
Abstract : Objective: Systemic sclerosis (SSc) is a clinically heterogeneous disease characterized by increased collagen accumulation and skin stiffness. Our previous work has demonstrated that transforming growth factor β (TGFβ) induces extracellular matrix (ECM) modifications through lysyl oxidase– like 4 (LOXL‐4), a collagen crosslinking enzyme, in bioengineered human skin equivalents (HSEs) and self‐assembled stromal tissues (SAS). We undertook this study to investigate cutaneous fibrosis and the role of LOXL‐4 in SSc pathogenesis using HSEs and SAS. Methods: SSc‐derived dermal fibroblasts (SScDFs; n = 8) and normal dermal fibroblasts (NDFs; n = 6) were incorporated into HSEs and SAS. These 3‐dimensional skin‐like microenvironments were used to study the effects of dysregulated LOXL‐4 on ECM remodeling, fibroblast activation, and response to TGFβ stimulation. Results: SScDF‐containing SAS showed increased stromal thickness, collagen deposition, and interleukin‐6 secretion compared to NDF‐containing SAS ( P < 0.05). In HSE, SScDFs altered collagen as seen by a more mature and aligned fibrillar structure ( P < 0.05). With SScDFs, enhanced stromal rigidity with increased collagen crosslinking ( P < 0.05), up‐regulation of LOXL4 expression ( P < 0.01), and innate immune signaling genes were observed in both tissue models. Conversely, knockdown of LOXL4 suppressed rigidity, contraction, and α‐smooth muscle actin expression in SScDFs in HSE, and TGFβ‐induced ECM aggregation and collagen crosslinking in SAS. Conclusion: A limitation to the development of effective therapeutics in SSc is the lack of in vitro human model systems that replicate human skin. Our findings demonstrate that SAS and HSE can serve as complementary in vitro skin‐like models for investigation of the mechanisms and mediators that drive fibrosis in SSc and implicate a pivotal role for LOXL‐4 in SSc pathogenesis.